Impact of sea-salt on morpho-physiological and biochemical responses in banana (Musa acuminata cv. Berangan) - Mazumdar, Purabi; Lau, Su Ee; Singh, Pooja; Takhtgahi, Hossein Mirzaei; Harikrishna, Jennifer Ann (Springer, 2019)
Banana is often grown in coastal-regions, and while known for its sensitivity towards seawater, little is documented on the effect of sea-salt on the growth, physiology and metal homeostasis. Here we report that banana plantlets exposed to sea-salt at extreme (average seawater concentration; 52.7 dS m−1), severe (28.5 dS m−1) or moderate (10.2 dS m−1) salinity levels had reduced root length (2.0–6.0-fold), plant height (1.2–1.6-fold), leaf number (2.0–2.3-fold) and leaf area (3.3–4.0-fold) compared to control plantlets. Degradation of pigments (total chlorophyll: 1.3–12.3-fold, chlorophyll a: 1.3–9.2-fold; chlorophyll b: 1.3–6.9-fold lower and carotenoids: 1.4–3.7-fold lower) reflected vulnerability of photosystems to salt stress. Relative water content showed a maximum decrease of 1.5-fold in salt stress. MDA analysis showed sea-salt exposure triggers 2.3–3.5-fold higher lipid peroxidation. Metal content analysis showed a 73-fold higher Na value from roots exposed to extreme salinity compared to control plantlets. While phenotype was clearly affected, moderate salinity showed no significant alteration of macro (N, P, K and Ca) and micro (Fe, Mn and Cu) metal content. The antioxidant enzymes: SOD (3.2-fold), CAT (1.7-fold) and GR (6-fold) showed higher activity at moderate salinity level compared to control plantlets but lower activity at severe (SOD: 1.3-fold; CAT: 1.5-fold; GR: 2-fold lower) and extreme seawater salinity (SOD: 1.5; CAT: 1.9; GR: 1.3-fold lower). Mild changes in growth and physiology at sea-salt levels equivalent to moderate seawater flooding, indicate that banana will survive such flooding, while extreme seawater inundation will be lethal. This data provides a reference for future salinity-mediated work in banana. © 2019, Prof. H.S. Srivastava Foundation for Science and Society.